CHANGES IN QUALITY OF LIFE AS A CRITERION OF EFFECTIVENESS OF HOSPITAL TREATMENT - V.К. Yur'ev; M.Kh. Saifulin ("Paediatrician" Publishers LLC, 2009)
The quality of life in 120 children and adolescents with different types of tuberculosis, treated in Astrakhan Regional Children's sanatorium for the Treatment of Patients with All Types of Tuberculosis was evaluated with PedsQL (value 4.0) questionnaire. Authors estimated an initial level of a quality of life before the beginning of hospital treatment and right after its finishing. They analyzed changes in quality of life in children of different age, boys and girls separately, and according to the subjective estimation of parents (tutors) and children themselves, and also according to the separated scales of functioning. Key words: children, tuberculosis, quality of life, hospital treatment. (Voprosy sovremennoi pediatrii - Current Pediatrics. 2009;8(6):7-11)